PELATIHAN PENGUKURAN STATUS GIZI BALITA SEBAGAI UPAYA PENCEGAHAN STUNTING SEJAK DINI PADA IBU DI DUSUN RANDUGUNTING, SLEMAN, DIY - Khoiriyah Isni; Siti Muthia Dinni (LP2M Universitas Hasanuddin, 2020)
Toddler Nutrition Status Measurement Training as an Early Prevention of Stunting to Mothers in Dusun Randugunting, Sleman, DIYAbstract. Dusun Randugunting has the highest number of toddlers, among other hamlets in the area of Tamanmartani Village, Kalasan, Sleman. It is very risky contributing to the number of cases of stunting if parents pay less attention to children's health and development. The role of parents as the vanguard and take full responsibility for children's health problems, especially nutrition problems for children under five. Parents should have sufficient knowledge and skills to be able to measure the nutritional status of infants by using a simple anthropometric method. The purpose of this training activity is to increase awareness of target skills in early detection of independent stunting by using anthropometric methods. The method of implementing this community service activity uses a combination of education, training, and simulation methods. The targets are pregnant women, mothers with children under the age of five, and health cadres. The results of the implementation of the activity showed quite high enthusiasm from the target. The showed that there were differences in the mean scores before and after the training. It hoped to increase parental awareness on toddler nutrition health problems so that it can have an impact and can contribute to reducing the number of stunting cases in Indonesia.Keywords: Antropometri, stunting, nutrition, randugunting.Abstrak. Dusun Randugunting memiliki jumlah balita terbanyak diantara Dusun lain di wilayah Desa Tamanmartani, Kalasan, Sleman. Hal ini sangat berisiko menyumbang angka kasus stunting apabila para orang tua kurang memperhatikan kesehatan dan tumbuh kembang anak. Peran orang tua sebagai garda terdepan dan bertanggung jawab penuh terhadap masalah kesehatan anak, terutama masalah gizi balita. Seyogyanya orang tua memiliki pengetahuan dan keterampilan cukup memadai untuk dapat melakukan pengukuran status gizi balita dengan menggunakan metode antropometri sederhana. Tujuan dari kegiatan pelatihan ini adalah meningkatkan kesadaran akan keterampilan sasaran dalam deteksi dini stunting secara mandiri dengan menggunakan metode antropometri. Metode pelaksanaan kegiatan pengabdian ini menggunakan gabungan dari metode edukasi, pelatihan, dan simulasi. Sasarannya adalah ibu hamil, ibu yang memiliki anak usia dibawah lima tahun, dan kader kesehatan. Hasil pelaksanaan kegiatan menunjukkan antusiasme yang cukup tinggi dari sasaran. Harapannya melalui kegiatan ini dapat meningkatkan kesadaran orang tua dalam masalah kesehatan gizi balita, sehingga berdampak dan dapat berkontribusi mengurangi angka kasus stunting di Indonesia.Kata kunci: Antropometri, stunting, gizi, balita, randugunting.